Now hiring : a manager's guide to employing applicants with a criminal history - Young, Nicole C. Jones (Emerald Publishing Limited, 2022)
As organizations grapple with the challenges of hiring, they must also consider how they will engage with some of the most marginalized individuals in our society, such as individuals who have a criminal history. Many individuals are interested in returning to the workplace after obtaining a conviction. However, many of these individuals will encounter substantial barriers and exclusion when attempting to access employment in various occupations and industries. For our society to function, all individuals must have an opportunity to positively contribute, and organizations can no longer sit on the side-lines. Organizations have a responsibility to engage in hiring practices that encourage entry, not exclusion. Now Hiring allows readers to consider their individual biases, as well as their organizational employment practices and processes, and assess how these factors may be altered to increase hiring for individuals with a criminal history. Young encourages readers to think more broadly about the role of organizations and the responsibility that organizations have beyond their immediate stakeholders. Most importantly, Now Hiring prompts conversation and serves as a reminder that our current system is not sustainable. As we await other long overdue changes to various systemic issues, organizations must figure out how do their part. Providing entry to the workplace after a criminal history is a place to start.